Increased Government Control of Buganda's Financial Sinews since the Revolution of 1966 - Nsibambi, Apolo (Public Administration and Development, 1971)
The quest for a more equitable allocation ofresources and income in all parts of Uganda, has gained more commitment, support and above all possibilities and credibility since the revolutionary changes which abolished "federalism" in Uganda and Buganda's special privileges and political hegemony. Indeed even before 1967 the Government was exposed to pressure from the "neglected" areas to rectify the imbalance of not only economic resources allocation but of political "goods" as well.! For example, members of the West Nile District Council proposed that their district should be represented in the cabinet, claiming that industries were being established only in the districts which were represented in the cabinet and that tractors were only given to such districts.e The determination of the government of Uganda to distribute the economic growth and social services has been boldly and publicly declared and reiterated. Only recently the Minister of Planning and Economic Development Mr. J. M. Okae who was touring Lango District, declared, "economic development of Uganda, is aimed at bringing those areas neglected by the British Administration in line with other parts of the country't.t He added, "during the colonial administration, some areas were not allowed to grow some crops, and others were not given the essential services."
Keywords: Government; Buganda; Financial Sinews